2005
DOI: 10.1007/bf02931468
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of recombinant group B streptococcal protein ScaAB and evaluation of its immunogenicity

Abstract: Group B streptococcal (GBS) gene encoding the putative lipoprotein and adherence factor ScaAB was cloned and expressed in E. coli. Recombinant ScaAB protein was isolated. Signal sequence of ScaAB was found to be cleaved in the E. coli host. ScaAB recombinant protein was immunogenic in mice and antibodies against this protein were discovered in mice sera after GBS infection. The perspectives of the use of ScaAB protein in GBS vaccine are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…6 About 30% of GBS possess the bac gene which can be predominantly found in the strains of serotypes I and II. 7 The ScaAB protein is the major surface lipoprotein similar to the lipoprotein receptor-associated antigen I (LraI) family.. 8,9 This protein is presented on the surface of gram-positive pathogens and closely related to PsaA protein of S pneumoniae which is considered a protein-based vaccine candidate against pathogenic pneumococci which are the most common cause of community-acquired pneumonia. 10 The ScpB1 protein represents the portion of C5a peptidase, which is contained among 100% of strains of group A and B streptococci, thus providing a universal target for vaccines against pathogenic streptococci.…”
Section: Introductionmentioning
confidence: 99%
“…6 About 30% of GBS possess the bac gene which can be predominantly found in the strains of serotypes I and II. 7 The ScaAB protein is the major surface lipoprotein similar to the lipoprotein receptor-associated antigen I (LraI) family.. 8,9 This protein is presented on the surface of gram-positive pathogens and closely related to PsaA protein of S pneumoniae which is considered a protein-based vaccine candidate against pathogenic pneumococci which are the most common cause of community-acquired pneumonia. 10 The ScpB1 protein represents the portion of C5a peptidase, which is contained among 100% of strains of group A and B streptococci, thus providing a universal target for vaccines against pathogenic streptococci.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Tettelin et al (2002) did not detect expression of SAG1533 (MtsA) on the GBS surface using FACS analysis. However, it is worth noting that antibodies against MtsA were detected in sera of mice following infection with GBS (Vorobieva et al 2005). Antibodies to homologues of MtsA were also found in convalescent sera of humans with GAS and pneumococcal infections (Lei et al 2004;Rapola et al 2000) and in mice experimentally infected with GAS (Lei et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…pneumoniae infection [17]. Recently, Seon et al, 2017 have shown that attenuated pneumococcus pep27 mutant which protect mice against secondary pneumococcal challenge after influenza virus infection increased antibody titers against PspA protein but not type 2 capsular polysaccharide These data suggest that although pneumococcus is surrounded by a powerful polysaccharide capsule, at the stages of its reproduction, the internal proteins become available for molecular interaction and the antibodies forming against these proteins are protective [18].…”
Section: Discussionmentioning
confidence: 99%